2013
DOI: 10.1287/trsc.1120.0429
|View full text |Cite
|
Sign up to set email alerts
|

The Simultaneous Vehicle Scheduling and Passenger Service Problem

Abstract: Passengers using public transport systems often experience waiting times when transferring between two scheduled services. In this paper we propose a planning approach that seeks to obtain a favourable trade-off between the two contrasting objectives, passenger service and operating cost, by modifying the timetable. The planning approach is referred to as the simultaneous vehicle scheduling and passenger service problem (SVSPSP). The SVSPSP is modelled as an integer programming problem and solved using a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 21 publications
0
28
0
2
Order By: Relevance
“…The later approach is a combination of previously defined tools (Ceder, 2007) to compute timetables with even loads, timetables with even headways, and vehicle schedules with minimum operational costs. Petersen et al (2013) formulate a partial integration of TNT and MDVSP minimizing the weighted sum of the costs of vehicles usage and passenger transfers. The authors consider metatrips which are a sets of trips that contains an original trip of the initial timetable and also contains the ''same trip'' but with different departure times.…”
Section: Integrating Transit Network Timetabling and Vehicle Schedulimentioning
confidence: 99%
“…The later approach is a combination of previously defined tools (Ceder, 2007) to compute timetables with even loads, timetables with even headways, and vehicle schedules with minimum operational costs. Petersen et al (2013) formulate a partial integration of TNT and MDVSP minimizing the weighted sum of the costs of vehicles usage and passenger transfers. The authors consider metatrips which are a sets of trips that contains an original trip of the initial timetable and also contains the ''same trip'' but with different departure times.…”
Section: Integrating Transit Network Timetabling and Vehicle Schedulimentioning
confidence: 99%
“…During the transfer, passengers spend a lot of time waiting for connecting bus that serves on the line without well-designed timetable. Petersen et al (2013) reported that the waiting time for one transfer is an average of about 9.75 min on each weekday in the Greater Copenhagen area. Therefore, a well-designed timetable, with good coordination between buses so that passengers can enjoy smooth transfers with minimal delay, is quite important for an attractive bus transit service.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Service time estimation could help in the estimation and prediction of bus travel time (Furth and Muller, 2007), and arrival and departure time forecasts of intelligent transportation systems could become more precise if service time at bus stops is modeled (Shalaby and Farhan, 2004;Yu et al, 2011). Service time estimation are vital to daily operations, such as bus scheduling (Petersen et al, 2012;Ceder, 2011) and headway control (Sun and Hickman, 2008;Delgado et al, 2012). Moreover, bus service time estimation plays an vital role in transit network design (Cipriani et al, 2011;Bagloee and Ceder, 2011;Yu et al, 2012;Wu et al, 2015;Zhang et al, 2014;Yao et al, 2014;Amiripour et al, 2014;Nayeem et al, 2014) and transit assignment analysis (Szeto et al, 2011;Hamdouch et al, 2011;Leurent et al, 2014).…”
Section: Introductionmentioning
confidence: 99%